Blood Iron Status in Dairy Cows during Early Lactation - Relationship with Hematological, Biochemical, Endocrine and Inflammatory Response - Grubač, Siniša; Cincović, Marko R.; Djoković, Radojica; Majkić, Mira; Maja Došenović Marinković,; Petrović, Miloš; Nikolić, Sandra; Starič, Jože; Prodanov Radulović, Jasna (Acta Scientiae Veterinariae, 2024)
Background: Iron (Fe) is microelement, essential to ensure some metabolic physiological process. Although Fe is a stable element in the body that is tightly regulated, metabolic stress, lipolysis, ketogenesis, endocrine change, insulin resistance and inflammation in early lactation can influence Fe status in blood. The objectives of this experiment were to determine the Fe status of cows in early lactation and determine whether measures of Fe status were in relation with hematological, metabolic, endocrine and inflammatory response in cows during early lactation. Materials, Methods and Results: The experiment included 30 healthy cows in the 1st 6 weeks of lactation. Laboratory analysis includes determination of Fe status (blood Fe, unsaturated iron-binding capacity (UIBC), total iron-binding capacity (TIBC), transferrin saturation percentage (TS%) and metabolic response of cows (complete blood count, non-esterified fatty acids (NEFA), beta-hydroxybutyrate (BHB), cholesterol, triglycerides, glucose, total bilirubin (TBIL), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), cortisol, T3, T4, insulin, RQUICKIBHB, TNF-α, and haptoglobin). Blood samples were collected by puncture of coccygeal vein. Fe increased from the 1st to the 6th week of lactation, with significantly lower concentrations in the 1st 2 weeks of the experiment (P < 0.01). TIBC and UIBC were lower in 1st 2 or 3 weeks of experiment (P < 0.01), while the TS% was unchanged. Hematological response included a significant lower MCV and HCT (P < 0.01) and tendency to decrease HGB and RBC (P < 0.1) in 1st 3 weeks of lactation compared to 2nd 3 weeks. WBC and PLT was unchanged, but NLR was higher in 1st 3 weeks of lactation (P < 0.05). Metabolic response was characterized by higher concentration of NEFA, BHB, TBIL, AST, GGT (P < 0.01) and NEFA:CHOL ratio (P < 0.05), and lower concentration of GLU, TGC, CHOL (P < 0.01) and ALB (P < 0.05) in 1st 2 or 3 weeks of lactation compared to period from 4 to 6 week. Endocrine response included lower concentration of insulin (P < 0.01), T3 and T4 (P < 0.1), and higher concentration of cortisol and RQUICKIBHB index of insulin resistance (P < 0.01) in 1st 2 or 3 weeks of experiment compared to period from 4 to 6 weeks. Inflammatory response included higher concentration of TNF-α and haptoglobin (P < 0.01) in 1st 2 or 3 weeks of experiment compared to period from 4 to 6 weeks. Fe concentration showed significant positive correlation with TIBC, UIBC, HGB, MCV, GLU, T3, T4 and INS and negative correlation with NLR, NEFA, BHB and RQUICKIBHB. TIBC and UIBC showed negative correlation with TBIL, AST, GGT, and NEFA:CHOL ratio and positive with ALB and TGC. Fe showed negative correlation with TNF-α, while TIBC and UIBC showed negative correlation with haptoglobin. Metabolic and inflammatory parameters had higher magnitude of change when Fe was extrapolated on deficit level (9 μmol/L), compared to TIBC, UIBC, TS% and red blood cell parameters as functional indicators of Fe status. Discussion: Fe, TIBC and UIBC showed significant change in 1st 6 weeks of lactation. Decrease in Fe in cows could be related to general homeorhetic adaptation to the onset of lactation, since Fe correlates with indicators of lipolysis, ketogenesis, and endocrine parameters. The lower TIBC and UIBC observed in cows in 1st 3 weeks when Fe was lower is an unexpected finding, since Fe decrease usually increases TIBC and UIBC. TIBC correlates with hepatocytes indices of the functional status and lipid infiltration, so it is possible that TIBC decreases because of changes in lipid metabolism and acute response in the liver. Blood Fe, TIBC and UIBC can be useful indicators for assessing metabolic stress in early lactating cows. Keywords: cow, iron, early lactation, metabolic stress.